1998
DOI: 10.1037/0097-7403.24.3.254
|View full text |Cite
|
Sign up to set email alerts
|

Reward produced memories regulate memory-discrimination learning, extinction, and other forms of discrimination learning.

Abstract: In memory-discrimination learning, reward-produced memories are differentially rewarded such that they are the only stimuli available to support discriminative responding. Memory-discrimination learning was used in this study as follows: Reward-produced memories that were assumed to regulate instrumental performance in previously reported extinction and discrimination learning investigations were isolated and explicitly differentially reinforced (prior to a shift to extinction) in each of 4 runway investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Thus, when the agent does not receive reward during the extinction condition, it takes longer to determine that the extinction condition is different and will require a different situation representation (a “splitting” of the state). This is very compatible with Capaldi and colleagues’ suggestion that extinction arises from a discrimination between acquisition and extinction conditions (Capaldi, 1957, 1958; Capaldi & Birmingham, 1998; Capaldi & Lynch, 1968).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, when the agent does not receive reward during the extinction condition, it takes longer to determine that the extinction condition is different and will require a different situation representation (a “splitting” of the state). This is very compatible with Capaldi and colleagues’ suggestion that extinction arises from a discrimination between acquisition and extinction conditions (Capaldi, 1957, 1958; Capaldi & Birmingham, 1998; Capaldi & Lynch, 1968).…”
Section: Resultssupporting
confidence: 90%
“…Reinstatement by provision of unsignaled rewards (Pavlov, 1927;Rescorla, 2004;Robbins, 1990) can also be envisioned as a cued recall of the original state over other states. The presence of recent/available rewards is one of the most salient differences between states (Capaldi, 1957(Capaldi, , 1958Capaldi & Birmingham, 1998;Capaldi & Lynch, 1968).…”
Section: Relation To Other Models Of Extinction and Renewalmentioning
confidence: 99%
“…Under the XNY and ZNN series, Position 3 cues were associated with both Y (XNY series) and N (ZNN series), so position cues cannot explain either interevent anticipation on Trial 2 or discriminative responding on Trial 3. But item learning can by assuming that, on any given trial, animals may remember each of the reward events that occurred on one or more prior trials (see, e.g., Capaldi, 1992Capaldi, , 1994Capaldi & Birmingham, 1998). Specifically, in the XNY series, the rats remembered X and X+N on Trials 2 and 3, respectively, whereas, in the ZNN series, the rats remembered Z and Z + N, respectively on Trials 2 and 3.…”
mentioning
confidence: 99%
“…For example, in , the number of food pellets delivered in a one-way runway apparatus on Trial I indicated whether reward or nonreward would occur on Trial 2. Results showed that discriminative responding on Trial 2 was much better the larger the difference in reward magnitude between the two trials .There is nowevidencethat reward-produced memories may serve an important signaling function in discrimination learning and extinction (Capaldi & Birmingham, 1998).…”
Section: Appetitive Conditioningmentioning
confidence: 94%
“…The signaling properties offood have also been studied in appetitive conditioning by Capaldi and his associates (Capaldi 1994;Capaldi, Alptekin, Miller, & Birmingham, 1997;Capaldi & Birmingham, 1998). For example, in , the number of food pellets delivered in a one-way runway apparatus on Trial I indicated whether reward or nonreward would occur on Trial 2.…”
Section: Appetitive Conditioningmentioning
confidence: 99%